Risk of Malignancy Index 4 (RMI4) and Risk of Malignancy Index 3 (RMI3) as Diagnostic Tests for Adnexal Tumor: Risk of Malignancy Index 4 (RMI4) dan Risk of Malignancy Index 3 (RMI3) sebagai Alat Diagnostik untuk Tumor Adneksa - Tatit Nurseta; Yahya Irwanto; Nugrahanti Prasetyorini; Bambang Rahardjo; I Wayan Subage (Indonesian Journal of Obstetrics and Gynecology, 2020)
Objective: Comparing scoring with RMI3 and RMI4 in establishing the diagnosis of adnexal tumour in RSUD Dr. Saiful Anwar Malang.Methods: Prospective cohort study with samples of all patients suspected of having an adnexal tumour diagnosed in gynecology policlinic using gynecological oncology policlinic medical records at RSUD Dr. Saiful Anwar in the form of age, demographics, menopause status, Ca125, ultrasound results.Results: Between the RMI3 results and the results of histopathology, a contingency coeffi cient of 0.596 was obtained with a p-value of 0.000015 (p <0.05), with a PPV of 83%, an NPV of 91%. Between the RMI4 results and the histopathology results, a contingency coeffi cient of 0.657 with a p-value of 0.0000004 (p <0.05) was obtained, with a PPV of 92%, NPV of 95%. On the ROC curve, the area of the predicted results using the RMI4 score is higher than the RMI3 score.Conclusions: Using the RMI4 score results in more accurate predictions than the RMI3 score in detecting adnexal tumour malignancies.Keywords: adnexal tumours, diagnostic tests, ovarian tumours, risk of malignancy index, ultrasound. Abstrak Tujuan: Membandingkan Skoring RMI3 dan RMI4 dalam menegakkan diagnosis tumor adneksa di RSUD dr. Saiful Anwar Malang.Metode: penelitian kohort prospective dengan sampel semua pasien yang dicurigai menderita tumor adneksa yang didiagnosis di poli Ginekologi menggunakan data rekam medis poli Ginekologi Onkologi RSUD dr. Saiful Anwar berupa usia, demografi , status menopause, Ca125, hasil USG.Hasil: Antara hasil RMI3 dengan hasil hispatologi, didapatkan koefi sien kontingensi sebesar 0,596 dengan p-value 0,000015 (p<0,05), dengan PPV 83%, NPV 91%. Antara hasil RMI4 dengan hasil histopatologi, didapatkan koefisien kontingensi sebesar 0,657 dengan p-value 0,0000004 (p<0,05), dengan PPV 92%, NPV 95%. Pada kurva ROC, luas area hasil prediksi dengan menggunakan skor RMI4 lebih tinggi daripada skor RMI3.Kesimpulan: Menggunakan skor RMI4 menghasilkan prediksi yang lebih tepat daripada skor RMI3 dalam mendeteksi keganasan tumor adneksa.Kata kunci: risk of malignancy index, tumor adneksa, tumor ovarium, uji diagnostik, USG.